Electric and hybrid vehicles power sources, models, sustainability, infrastructure and the market - Pistoia, G. (Elsevier, 2010)
This multi-author, 670-page handbook provides information on alternative vehicular power systems, encompassing advances in the rapidly evolving battery, hybrid and fuel cell technology domains. Vehicles based on these technologies are described in terms of performance, fuel economy, environmental impact, energy sources and costs, and are extensively compared and contrasted to conventional vehicles. For the most advanced concepts in development (fuel cell and long-range electric vehicles), the issue of recharging infrastructure is addressed, as are case studies of alternative vehicles proposed b.
Keywords: Electric vehicles.; Hybrid electric vehicles.; elektronické knihy; electronic books